2022
DOI: 10.3389/fendo.2022.918350
|View full text |Cite
|
Sign up to set email alerts
|

The Extraglycemic Effect of SGLT-2is on Mineral and Bone Metabolism and Bone Fracture

Abstract: Type 2 diabetes mellitus (T2DM) is a risk factor for osteoporosis. The effects of T2DM and anti-diabetic agents on bone and mineral metabolism have been observed. Sodium–glucose co-transporter 2 inhibitors (SGLT-2is) promote urinary glucose excretion, reduce blood glucose level, and improve the cardiovascular and diabetic nephropathy outcomes. In this review, we focused on the extraglycemic effect and physiological regulation of SGLT-2is on bone and mineral metabolism. SGLT-2is affect the bone turnover, microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 82 publications
0
9
0
1
Order By: Relevance
“…Ageing can predispose kidney state into acute and chronic kidney disease. [18][19][20] lowering blood glucose, [22][23][24] the off-target roles of SGLT2i were independent of lowering glucose. 18,19,25 The renal anti-senescence role of SGLT2i has been reported, most likely related to increasing the expression of klotho.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ageing can predispose kidney state into acute and chronic kidney disease. [18][19][20] lowering blood glucose, [22][23][24] the off-target roles of SGLT2i were independent of lowering glucose. 18,19,25 The renal anti-senescence role of SGLT2i has been reported, most likely related to increasing the expression of klotho.…”
Section: Discussionmentioning
confidence: 97%
“…SGLT2i mainly focus on the sodium‐glucose cotransporter distributed on proximal tubular cells, through promoting the excretion of glucose to lower blood glucose and to exert beneficial effects 21 . Although SGLT2i mainly focus on regulating physiologically glucose level, several researches have demonstrated that SGLT2i played beneficial roles transcending lowering blood glucose, 22–24 the off‐target roles of SGLT2i were independent of lowering glucose 18,19,25 . The renal anti‐senescence role of SGLT2i has been reported, most likely related to increasing the expression of klotho 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of diabetes medications on bone and mineral metabolism have been observed. SGLT2 inhibitors may not increase the risk of bone fracture, but their effects are controversial and require further study [ 64 ]. SGLT2 inhibitors are also thought to promote renal phosphate reabsorption, increase fibroblast growth factor 23 and PTH, and act by decreasing active vitamin D, causing calciuria [ 65 ]; however, the effects of diabetes medications on bone health need further study.…”
Section: Discussionmentioning
confidence: 99%
“…In observational studies, the relative fracture risk for SGLT2 inhibitors was compared with other hypoglycemic drugs currently in use, such as DPP-4 inhibitors, (11)(12)(13)(14)(15) sulphonylurea, (16) and GLP-1 receptor agonists, (17)(18)(19) and most studies yielded negative results. (46) Compared with observational studies, which may be subject to potential confounders and draw relative risks, the MR study is less likely to be affected by confounders and directly evaluate the causal effect of SGLT2 inhibition on fracture risk.…”
Section: Discussionmentioning
confidence: 99%